Visualization of Kepler's laws of planetary motion. (25th January 2017) - Lu, Meishu; Su, Jun; Wang, Weiguo; Lu, Jianlong
Abstract: For this article, we use a 3D printer to print a surface similar to universal gravitation for demonstrating and investigating Kepler's laws of planetary motion describing the motion of a small ball on the surface. This novel experimental method allows Kepler's laws of planetary motion to be visualized and will contribute to improving the manipulative ability of middle school students and the accessibility of classroom education.